Logic Pro X audio and music production - Cousins, Mark 1972-; Hepworth-Sawyer, Russ (Focal Press, 2014)
From initial demos to mixing and mastering, seasoned authors Mark Cousins and Russ Hepworth-Sawyer show you how to get the most from Logic Pro X. By exploring the essential workflow and the creative possibilities offered by Logic's virtual instruments and effects, Logic Pro X: Audio and Music Production leads you through the music creation and production process, giving you all the tips and tricks used by the pros to create release-quality recordings. Using full color screenshots throughout, alongside related boxouts that expand on the key concepts, Logic Pro X: Audio and Mu.
Includes bibliographical references and index. - Print version record
Keywords: Logic (Computer file); Digital audio editors; Éditeurs audionumériques; MUSIC; Instruction & Study; Theory